2017
DOI: 10.1063/1.4993560
|View full text |Cite
|
Sign up to set email alerts
|

Flexible strain sensors with high performance based on metallic glass thin film

Abstract: Searching strain sensitive materials for electronic skin is of crucial significance because of the restrictions of current materials such as poor electrical conductivity, large energy consumption, complex manufacturing process, and high cost. Here, we report a flexible strain sensor based on the Zr 55 Cu 30 Ni 5 Al 10 metallic glass thin film which we name metallic glass skin. The metallic glass skin, synthesized by ion beam deposition, exhibits piezoresistance effects with a gauge factor of around 2.86, a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…prevention, 1,2 and thus has received extensive attention. This great demand inspires growing research enthusiasm for the development of robust, high sensitivity, and wide range strain sensor technology in scientific circles and industry.…”
mentioning
confidence: 99%
“…prevention, 1,2 and thus has received extensive attention. This great demand inspires growing research enthusiasm for the development of robust, high sensitivity, and wide range strain sensor technology in scientific circles and industry.…”
mentioning
confidence: 99%
“…However, how to use the kirigami structures to develop optoelectronic devices or wearing devices is still challenging. Because of the unique properties, it is expected more functional devices using MGs will be developed in future, such as large elasticity, light weight, wearable sensors and optoelectronic devices [19,89,91].…”
Section: Discussionmentioning
confidence: 99%
“…The stretchable kirigami MG structures are useful for developing mechanical meta-materials and optoelectronic devices with extended cycle life. For example, Xian et al have reported some MG film skins with a piezoresistance effect, large strain range and good conductivity [91]. The use of kirigami structures to develop electronic skins may further enhance the stretchability for wearable devices.…”
Section: Kirigami Mg Structuresmentioning
confidence: 99%
See 2 more Smart Citations